Comparing And Analyzing the Translation of the Cover Song Angels Like You by Luna Casano with the Translation by ChatGPT - Joliastri, Febrila Ayu; Baharuddin, Baharuddin; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to analyze the translation strategies employed by Luna Casano in translating the song “Angels Like You” into Indonesian and to compare the resulting translation with those generated by ChatGPT using three different prompts. Utilizing Peter Newmark’s (1988) framework of translation strategies, the research adopts a descriptive qualitative approach. The findings reveal that Luna Casano predominantly uses Literal Translation and Free Translation (each accounting for 30% of the total), followed by Communicative Translation (25%), Faithful Translation (10%), and Idiomatic Translation (5%). Notably, Word-for-word, Semantic, and Adaptation strategies are absent from her translation. In contrast, the quality of ChatGPT’s translations is significantly influenced by the specificity of the prompts provided. Among the three prompts tested, Prompt 3—which instructs the AI to produce a poetic and singable version—yields the most comparable output to Luna Casano’s translation. This study concludes that while AI-based tools such as ChatGPT can generate accurate and stylistically appropriate translations when guided effectively, human involvement remains crucial in preserving the emotional depth, musicality, and aesthetic value inherent in song lyrics. It is recommended that future studies explore the application of similar translation strategies in other forms of artistic texts, such as poetry or drama, to further examine the evolving role of AI in literary and creative translation.